Recombinant Bacillus subtilis Improves Growth and Protein Utilization and Regulates PI3K/AKT/TOR Pathway-Related Genes in Chinese Mitten Crab (Eriocheir sinensis) - Yongmin Li; Shengyu Gao; Wenbin Liu; Xiangfei Li; Guangzhen Jiang; Chaofan He (Animals, 2025)
The inclusion of suitable quantities of plant protein hydrolysates in feed enhances the growth performance of aquatic animals, a benefit closely linked to the bioactive peptides generated during plant protein hydrolysis. In our previous study, we developed a recombinant Bacillus subtilis expressing the P4’ peptide of cottonseed meal (P4’ peptide-bearing B. subtilis). We observed that the addition of this recombinant B. subtilis at a dose of 109 CFU/kg to the diet of E. sinensis produced a significant growth-promoting effect. The mechanism underlying this growth-promoting effect remains unclear. This experiment aimed to investigate the effects of feed supplementation with P4’ peptide-bearing B. subtilis on the growth performance, digestive enzyme activities, serum protein content, antioxidant-related enzyme activities, and genes associated with the PI3K/AKT/TOR pathway in the Chinese mitten crab (Eriocheir sinensis). A total of 240 crabs (mean body weight: 0.85 ± 0.01) were randomly assigned to three groups and provided with three distinct diets: one without B. subtilis (CON), one containing 109 CFU/kg of unmodified B. subtilis (BS9), and one with P4’ peptide-bearing B. subtilis (RBS9) at 109 CFU/kg. After 8 weeks of feeding, the BS9 and RBS9 groups had significantly increased specific growth rate, average body weight, muscle crude protein content, hemolymph total protein/albumin/globulin levels, hepatopancreatic digestive enzyme (protease and amylase) activities, and tor expression in crabs compared to the CON group. Conversely, muscle water content, hepatopancreatic ROS levels, and 4ebp-1 expression were significantly reduced. Furthermore, mean body weight, protein retention, muscle crude fat content, total hemolymphatic protein, and globulin content, as well as the hepatopancreatic expression of pi3k, tor, and s6k1, were significantly higher in the RBS9 group compared to the BS9 group. In contrast, the hepatopancreatic ROS level exhibited a declining trend. The result demonstrated that compared to unmodified B. subtilis, incorporating 109 CFU/kg P4’ peptide-bearing B. subtilis into the feed significantly enhanced the growth performance and protein deposition in E. sinensis. This enhanced effect coincided with the upregulation of key PI3K/AKT/TOR pathway genes (pi3k, tor, s6k1) and the downregulation of 4ebp-1 in the hepatopancreatic cells, indicating a potential role of this pathway in mediating the observed growth promotion.